2016
DOI: 10.1016/j.ijrobp.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Maximum Dose on White Matter Fiber Bundles Using Longitudinal Diffusion Tensor Imaging

Abstract: Purpose Previous efforts to decrease neurocognitive effects of radiation focused on sparing isolated cortical structures. We hypothesize that understanding temporal, spatial and dosimetric patterns of radiation damage of whole brain white matter (WBWM) after partial brain irradiation might also be important. Therefore, we carried out a study to develop the methodology to assess radiotherapy-induced damage to WBWM bundles. Methods An atlas-based, automated WM tractography analysis was implemented to quantify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 32 publications
1
25
1
Order By: Relevance
“…In patients with MCI, changes within the ventral cingulum are predictive of (and detectable prior to) hippocampal volume loss and memory performance [35]. While a previous study of radiation effects on white matter found dose sensitivity to DTI changes in the parahippocampal cingulum [36], we did not detect robust dose-sensitivity in this structure. Indeed the distinction between the dorsal and ventral aspects of the cingulum are rather arbitrary, and may vary by DTI atlas [25,32].…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In patients with MCI, changes within the ventral cingulum are predictive of (and detectable prior to) hippocampal volume loss and memory performance [35]. While a previous study of radiation effects on white matter found dose sensitivity to DTI changes in the parahippocampal cingulum [36], we did not detect robust dose-sensitivity in this structure. Indeed the distinction between the dorsal and ventral aspects of the cingulum are rather arbitrary, and may vary by DTI atlas [25,32].…”
Section: Discussioncontrasting
confidence: 66%
“…With respect to dose, a recent DTI study found that elongated white matter tracts after partial brain RT responded more to maximum dose rather than mean dose [36]. The possibility of serial structure response carries important implications for RT planning, as this suggests that limiting hot spots within a tract is more important than limiting the mean dose delivered to the entire structure.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on tissue-dose interaction, as the current one, aid in understanding radiation-induced cognitive decline, which may be the consequence of, but not restricted to, demyelination and loss of axonal integrity with increasing radiation doses. Research in neuroscience, especially on aging [47,48] and cognitive impairment [49,50] ROIs receiving certain dose levels or aim to avoid PVE by restricting the masking to connected voxels that only include WM structure by excluding voxels with FA lower than 0.2 [17,29,55].…”
Section: Discussionmentioning
confidence: 99%
“…We further assumed that tissue change relates linearly to the applied dose. While this framework is widely applied by the RT-community [17,29,55,75], these assumptions may only approximate the true underlying relations. Further biophysical modeling is .…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study found that diffusion changes in individual white matter bundles were associated with maximum dose to those tracts, implying serial radiation injury. 149 There also appears to be regional susceptibility of white matter damage. A study of medulloblastoma survivors found greater diffusion changes in the frontal versus parietal lobes.…”
Section: Neuroimaging Evidence For Radiation Induced Cns Changesmentioning
confidence: 99%